Or construction project: from planning to execution. - Worley DJ; Hohler SE (AORN Journal, 2008)
OPERATING ROOM RENOVATION PROJECTS require planning and collaboration among physicians, hospital staff members, and vendors. RENOVATION INVOLVES many details, from how many electrical plugs to install in each OR to integration of the latest technologies. DETAILS OF A MULTIPHASE OR renovation project undertaken at Saint Francis Medical Center in Cape Girardeau, MO, provide information and tools that any facility planning a renovation can use.